PENGARUH JUS SEMANGKA (Citrullus Vulgaris Schrad) TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI PRIMER - Lavintang, Mutiara; Erwin, Erwin; Dewi, Yulia Irvani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Current changes in patterns of disease that were originally dominated by infectious diseases turned to noncommunicable diseases such as hypertension. This study aims to determine the effect of watermelon juice (Citrullus Vulgaris Schrad) on the blood pressure of patients with primary hypertension. The design of this research is